Exploring the Potential of Traditional Javanese Gamelan Music as an Early Screening Tool for Monitoring Fetal Well-being During the Third Trimester of Pregnancy - Fajrin, Rachma Aisyiyah Yoshida; Yudianti, Ika; Apsari, Duhita Dyah (Futurity Medicine, 2025)
Fetal movement is a recognised marker of fetal well-being, and its monitoring plays a crucial role in prenatal care. Simple, non-invasive, and culturally-appropriate stimulation methods are needed, particularly in settings with limited access to advanced fetal monitoring technologies. Aims: This study aims to explore the potential use of traditional Javanese gamelan music as an early screening tool to monitor fetal well-being during the third trimester of pregnancy. Study design: A pre-experimental study design using a one-group pretest post-test method was applied to ≥28 weeks low risk pregnant women (n=30). Data were collected through two measurements: the first during a 30-minute observation before the exposure to Javanese gamelan music, and the second during a 30-minute period while the participants listened to the music. Place and duration of study: The data for the study was collected from an independent midwifery practice in Malang during August 2022. Methodology: The used sampling technique was the total sampling technique. The variables studied were Traditional Javanese Gamelan instrumental as independent variable and the frequency of fetal movement as dependent variable measured with kick counter application. Results: The average of fetal movement frequency before the intervention was 6.4 movements, and during the intervention, it increased to 13.3 movements. Data analysis was performed using a paired t-test, which yielded a calculated t-value of 4.79, exceeding the critical t-value of 1.73. The result was statistically significant, with a p-value of 0.000, which is less than the alpha level of 0.05 [95% CI]. Scientific novelty: While previous research has commonly utilised gamelan music to stimulate fetal intelligence, this study explores its potential as a simple, local wisdom-relevant, and non-invasive auditory stimulation tool to aid in the early detection of fetal well-being issues during the third trimester of pregnancy. Conclusion: Traditional Javanese gamelan music may serve as a simple instrument for pregnant women to stimulate fetal movements and support self-monitoring of fetal well-being during the third trimester.